Linkages between modern benthic foraminiferal assemblages and environmental conditions at continental slope depths: From Baffin Bay to the Labrador Sea - Joanna Davies; Anne Jennings; Alice Carter-Champion; William J. D'Andrea; Cara Fritz; Erin E. Gregory; David J. Harning; Robert Kelleher; Alan C. Mix; Katherine Stelling; Joseph S. Stoner; Maureen H. Walczak; et al. (Marine Micropaleontology, 2025)

A framework for reconstructing marine heatwaves from individual foraminifera in sedimentary archives - Casey Saenger; Carlos Jimenez-Diaz; Alexander Gagnon; Alan Mix; Andrew Ross; Tongtong Xu (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are warm sea surface temperature (SST) anomalies with substantial ecological and economic consequences. Observations of MHWs are based on relatively short instrumental records, which limit the ability to forecast these events on decadal and longer timescales. Paleoclimate reconstructions can extend the observational record and help to evaluate model performance under near future conditions, but paleo-MHW reconstructions have received little attention, primarily because marine sediments lack the temporal resolution to record short-lived events. Individual foraminifera analysis (IFA) of paleotemperature proxies presents an intriguing opportunity to reconstruct past MHW variability if strong relationships exist between SST distributions and MHW metrics. Here, we describe a method to test this idea by systematically evaluating relationships between MHW metrics and SST distributions that mimic IFA data using a 2000-member linear inverse model (LIM) ensemble. Our approach is adaptable and allows users to define MHWs based on multiple duration and intensity thresholds and to model seasonal biases in five different foraminifera species. It also allows uncertainty in MHW reconstructions to be calculated for a given number of IFA measurements. An example application of our method at 12 north Pacific locations suggests that the cumulative intensity of short-duration, low-intensity MHWs is the strongest target for reconstruction, but that the error on reconstructions will rely heavily on sedimentation rate and the number of foraminifera analyzed. This is evident when a robust transfer function is applied to new core-top oxygen isotope data from 37 individual Globigerina bulloides at a site with typical marine sedimentation rates. In this example application, paleo-MHW reconstructions have large uncertainties that hamper comparisons to observational data. However, additional tests demonstrate that our approach has considerable potential to reconstruct past MHW variability at high sedimentation rate sites where hundreds of foraminifera can be analyzed.

INTRODUCTION TO THE SPECIAL ISSUE. Paleoceanography: Lessons for a Changing World - Amelia Shevenell; Peggy Delaney; Katrin Meissner; Laurie Menviel; Alan Mix (Oceanography, 2020)

On Quantifying Stratigraphic, Chronologic, and Paleo Flux Uncertainties in Paleoceanography - Alan Mix (Oceanography, 2020)

TRIBUTE • Wallace S. Broecker (1931–2019) - Alan Mix (Oceanography, 2019)

“So Long, and Thanks for All the Fish” - Alan Mix (Oceanography, 2018)

Policies for a Member-Run Organization - Alan Mix (Oceanography, 2018)

30 Years of TOS and the Wisdom of Our Founders - Alan Mix (Oceanography, 2018)

On Mentoring of Graduate Students - Alan Mix (Oceanography, 2018)

Educating Undergraduates About the Ocean - Alan Mix (Oceanography, 2017)

Planning the Future of Ocean Sciences - Alan Mix (Oceanography, 2017)

Follow the Money - Alan Mix (Oceanography, 2017)

TOS—The Times They Are a Changin’… Again - Alan Mix (Oceanography, 2017)

Influences of extratropical water masses on equatorial Pacific cold tongue variability during the past 160 ka as revealed by faunal evidence of planktic foraminifers - Pai‐Sen Yu; Markus Kienast; Min‐Te Chen; Isabel Cacho; Jos Abel Flores; Mahyar Mohtadi; Alan C. Mix (Journal of Quaternary Science, 2012)
Glacial cooling (∼1–5°C) in the eastern equatorial Pacific (EEP) cold tongue is often attributed to increased equatorial upwelling, stronger advection from the Peru–Chile Current (PCC), and to the more remote subpolar southeastern Pacific water mass. However, evidence is scarce for identifying unambiguously which process plays a more important role in driving the large glacial cooling in the EEP. To address this question, here we adopt a faunal calibration approach using planktic foraminifers with a new compilation of coretop data from the eastern Pacific, and present new downcore variation data of fauna assemblage and estimated sea surface temperatures (SSTs) for the past 160 ka (Marine Isotope Stage (MIS) 6) from ODP Site 1240 in the EEP. With significant improvement achieved by adding more coretop data from the eastern boundary current, our downcore calibration results indicate that most of the glacial cooling episodes over the past 160 ka in the EEP are attributable to increased influence from the subpolar water mass from high latitudes of the southern Pacific. By applying this new calibration of the fauna SST transfer function to a latitudinal transect of eastern Pacific (EP) cores, we find that the subpolar water mass has been a major dynamic contributor to EEP cold tongue cooling since MIS 6. Copyright © 2012 John Wiley & Sons, Ltd.

Bias and uncertainty of δ13CO2 isotopic mixing models - Zachary E. Kayler; Lisa Ganio; Mark Hauck; Thomas G. Pypker; Elizabeth W. Sulzman; Alan C. Mix; Barbara J. Bond (Oecologia, 2010)